Stretchable conductive nanocomposites of low electrical percolation threshold for washable high-performance-interconnects - Kwag, Seungho; Ko, Youngpyo; Jeon, Jun-Young; Jang, Doojoon; Park, Minju; Choi, Yoohyeon; Cho, Jinhan; Kim, Heesuk (Royal Society of Chemistry, 2023)
Elastomer-based stretchable conductive composites of high electrical conductivity, mechanical stability and excellent adhesion to the substrates are essential as interconnects for stretchable electronics. Most previous composites require high percolation threshold concentration of metallic fillers to achieve high electrical conductivity, which in turn lowers their mechanical stability and adhesion to the targets. Herein, we propose a rationally designed stretchable conductive composite of low percolation threshold concentration with the aid of boron nitride (BN) as a non-conductive auxiliary filler. The BN introduction significantly increases the electrical conductivity of the composites by up to 9 orders of magnitude at 66 wt% Ag concentration. The percolation threshold Ag concentration of the composite without BNs is 63.3 wt% (14.8 vol%), whereas the introduction of 3 mu m h-BNs lowers the threshold concentration to 52.0 wt% (9.53 vol%), which is due to the effective attractive interaction between auxiliary BN and Ag particles. Furthermore, the exfoliated 3 mu m BNs lower the BN concentration to achieve similar electrical conductivity, thereby leading to improved electrical stability as well as excellent adhesion when bent or stretched. The composites have been successfully applied as stretchable electrical interconnects and maintain their performance even after repeated washings. These model studies provide an insight in that the inter-particle interaction between an auxiliary filler and a conductive filler is a key design parameter to reduce the percolation threshold concentration for high-performance stretchable conductive composites.